2017
DOI: 10.2147/copd.s140247
|View full text |Cite
|
Sign up to set email alerts
|

Asynchrony in respiratory movements between the pulmonary lobes in patients with COPD: continuous measurement of lung density by 4-dimensional dynamic-ventilation CT

Abstract: PurposeFour-dimensional dynamic-ventilation CT imaging demonstrates continuous movement of the lung. The aim of this study was to assess the correlation between interlobar synchrony in lung density and spirometric values in COPD patients and smokers, by measuring the continuous changes in lung density during respiration on the dynamic-ventilation CT.Materials and methodsThirty-two smokers, including ten with COPD, underwent dynamic-ventilation CT during free breathing. CT data were continuously reconstructed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Although previous studies indicated that ventilation defects could be detected as decreased changes in radiographic lung density [8,25], further studies are Respiration 2020;99:382-388 DOI: 10.1159/000506881 needed to confirm the relationship between pulmonary function and changes in radiographic lung density. Third, it has been reported that the synchrony of respiratory movements between the pulmonary lobes is limited or lost in patients with more severe airflow limitation in the study using 4-dimensional dynamic-ventilation CT [26]. Although this study focused on the rate of change in the lung area, future studies need to find indices that indicate nonuniformity in respiratory movement using dynamicventilatory DR and show their associations with respiratory function and symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…Although previous studies indicated that ventilation defects could be detected as decreased changes in radiographic lung density [8,25], further studies are Respiration 2020;99:382-388 DOI: 10.1159/000506881 needed to confirm the relationship between pulmonary function and changes in radiographic lung density. Third, it has been reported that the synchrony of respiratory movements between the pulmonary lobes is limited or lost in patients with more severe airflow limitation in the study using 4-dimensional dynamic-ventilation CT [26]. Although this study focused on the rate of change in the lung area, future studies need to find indices that indicate nonuniformity in respiratory movement using dynamicventilatory DR and show their associations with respiratory function and symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…In patients with COPD, the destruction of normal “mesh-like” structures of pulmonary tissue results in pulmonary emphysema and leads to a reduction of lung compliance, causing inhomogeneous transmission of lung motion during the respiratory cycle 14. Furthermore, the heterogeneous distribution of emphysematous changes and airway diseases also intensify the heterogeneity of lung movement during ventilation,1517 which has been clearly confirmed in recent studies using 4D dynamic-ventilation CT and other imaging techniques 1820. These recent studies have demonstrated the existence of asynchrony between the right and left lungs, between the proximal airways and lung, and among different lung lobes.…”
Section: Introductionmentioning
confidence: 71%
“…This study was also part of the Area-detector Computed Tomography for the Investigation of Thoracic Diseases (ACTIve) Study, a multicenter research alliance in Japan. Also, the subjects’ data utilized in this study were previously analyzed with a different objective for other research 20…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we believe that this FV curve pattern is associated with a poorer prognosis and reduced BMI. Observation of the movement of the lung using 4D CT analysis has been recently attracting attention [25]. Future studies using a detailed analysis of lung movement are warranted to prove and establish our hypothesis regarding the heterogeneous movement of the thorax in this category of patients.…”
Section: Discussionmentioning
confidence: 99%